Treated dentin matrix paste as a novel pulp capping agent for dentin regeneration. (15th February 2017) - Chen, Jinlong; Cui, Caiyun; Qiao, Xiangchen; Yang, Bo; Yu, Mei; Guo, Weihua; Tian, Weidong
Abstract: Regenerating dentin and preserving pulp vitality are the two key targets for the treatment of dental pulp exposure. Calcium hydroxide (CH), the widely used capping agent, may induce potential tunnel defect in reparative dentin and cause inflammation or even necrosis in pulp tissues. This study aimed to produce a novel pulp capping agent with better bioactivities. Treated dentin matrix (TDM) paste (TDMP) was fabricated consisting of TDM powder and aqueous TDM extract. The chemical and biological characteristics of TDMP were investigated, and its effect on the odontogenic differentiation of dental pulp stem cells explored at gene and protein level; the therapeutic effect for pulp exposure in miniature swine was further verified. TDMP possessed better biocompatibility with neutral pH value, significantly promoted the proliferation of dental pulp stem cells, and enhanced the gene and protein expressions of alkaline phosphatase, bone sialoprotein, dentin sialoprotein etc., compared with CH. In vivo pulp capping using TDMP presented the formation of continuous reparative dentin bridge thicker and denser than CH group. Moreover, pulp tissues under TDMP capping sites showed relatively slight angiectasis than those induced by CH. TDMP could achieve both dentin regeneration and vital pulp conservation, and might serve as a feasible substitute for CH in dental pulp repair procedure. Copyright © 2017 John Wiley & Sons, Ltd.